x-x/3=3/57: 12/19
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x-\frac{x}{3}=\frac{3}{57}:\frac{12}{19}\)
\(\Leftrightarrow x-\frac{x}{3}=\frac{1}{19}\)
\(\Leftrightarrow\frac{2x}{3}=\frac{1}{19}\)
\(\Leftrightarrow2x.19=1.3\)
\(\Leftrightarrow2x.19=3\)
\(\Leftrightarrow2x=\frac{3}{19}\)
\(\Leftrightarrow x=\frac{3}{38}\)
Vậy: \(x=\frac{3}{38}\)
\(x-\frac{x}{3}=\frac{3}{57}:\frac{12}{19}\)
\(\frac{3x}{3}-\frac{x}{3}=\frac{3}{57}.\frac{19}{12}\)
\(\frac{2x}{3}=\frac{1}{12}\)
\(2x.12=1.3\)
\(24x=3\)
\(x=\frac{3}{24}=\frac{1}{8}\)
Vậy \(x=\frac{1}{8}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{2}{5}-\frac{2}{5}x+\frac{1}{3}=x-\frac{7}{15}\)
\(\Leftrightarrow\frac{11}{15}-\frac{2x}{5}=x-\frac{7}{15}\)
\(\Leftrightarrow\frac{2x}{5}=x-\frac{7}{15}-\frac{11}{15}\)
\(\Leftrightarrow-\frac{2x}{5}=x-\frac{5}{6}\)
\(\Leftrightarrow-\frac{2x}{5}=x.5-\frac{5}{6}.5\)
\(\Leftrightarrow-2x=5x-6\)
\(\Leftrightarrow-2x=-5x-6-5x\)
\(\Leftrightarrow-7x=-6\)
\(\Rightarrow x=\frac{6}{7}\)
( x - 1/2 ) : 3/11 =11/4
(2x + 3/8 ) . 7/4 =-21/32
x - x/3 = 3/57 : 12/19
nhanhh giúp tui nha các babee
![](https://rs.olm.vn/images/avt/0.png?1311)
( x - 1/2 ) : 3/11 =11/4
x - 1/2 = 11/4 x 3/11
x - 1/2 = 3/4
x = 3/4 + 1/2
x = 5/4
Vậy x = 5/4
(2x + 3/8 ) . 7/4 =-21/32
2x + 3/8 = -21/32 : 7/4
2x + 3/8 = -3/8
2x = -3/8 - 3/8
2x = -3/4
x = -3/4 : 2
x = -3/8
Vậy x = -3/8
![](https://rs.olm.vn/images/avt/0.png?1311)
\(7:\frac{5.8.x-57}{19+3}=7.\frac{22}{40x-57}=1775\)
<=> \(\frac{154}{40x-57}=1775=>x=\frac{154+1775.57}{40}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
A = ( -4/5 + 4/3 ) + (-5/4 + 14/5) - 7/3
= 8/15 + 31/20 - 7/3
= 25/12 - 7/3
= -1/4
B = 8/3 x 2/5 x 3/8 x 10x 19/92
= 16/15 x 15/4 x 19/92
= 4x19/92
= 19/23
C = - \(\dfrac{5}{7}\) x \(\dfrac{2}{11}\) + \(\dfrac{-5}{7}\) x \(\dfrac{9}{14}\) + \(\dfrac{1}{57}\)
= - \(\dfrac{10}{77}\) - \(\dfrac{45}{98}\) + \(\dfrac{1}{57}\)
= - \(\dfrac{635}{1078}\) + \(\dfrac{1}{57}\)
= - \(\dfrac{36195}{61446}\) + \(\dfrac{1078}{61446}\)
= - \(\dfrac{35117}{61446}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (x.7 + 8) : 5 = 10
x.7 + 8 = 10.5
x.7 + 8 = 50
x.7 = 50 - 8
x.7 = 42
x = 42 : 7
x = 6
b) (x + 5).19 : 13 = 57
(x + 5).19 = 57 . 13
(x + 5).19 = 741
x + 5 = 741 : 19
x + 5 = 39
x = 39 - 5
x = 34
c) 4.(36 - 4.x) = 64
36 - 4x = 64 : 4
36 - 4x = 16
4x = 36 - 16
4x = 20
x = 20 : 4
x = 5
d) 7,6 : 19 . x = 3,2
0,4 . x = 3,2
x = 3,2 : 0,4
x = 8
e) (x : 2 + 50) : 5 = 12
x : 2 + 50 = 12 . 5
x : 2 + 50 = 60
x : 2 = 60 - 50
x : 2 = 10
x = 10 . 2
x = 20
g) 280 : (17 + 3.x) = 4
17 + 3x = 280 : 4
17 + 3x = 70
3x = 70 - 17
3x = 53
x = 53/3
h) 6.(28 - 8.x) = 72
28 - 8x = 72 : 6
28 - 8x = 12
8x = 28 - 12
8x = 16
x = 16 : 8
x = 2
i) (x - 15) : 3 : 12 = 6
(x - 15) : 3 = 6 . 12
(x - 15) : 3 = 72
x - 15 = 72 . 3
x - 15 = 216
x = 216 + 15
x = 231
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x-\frac{x}{3}=\frac{3}{57}:\frac{12}{19}\)
\(x-\frac{x}{3}=\frac{3}{57}\times\frac{19}{12}\)
\(x-\frac{x}{3}=\frac{1}{12}\)
\(\Rightarrow12x-4x=1\)
\(\Rightarrow8x=1\)
\(\Rightarrow x=\frac{1}{8}\)